Pembangunan dan Pariwisata Perubahan Masyarakat di Kawasan Objek Wisata Way Belerang - Irsan PhD (Balitbangda Provinsi Lampung, 2015)
This jornal stressed to livelihoods changed of Bumi Agung society at Way Belerang tourist attraction at Lampung Selatan Regency. It’s seen from strategies are created and developed by citizens in line with tourism development. Since tourism development was founded, livelihoods of Bumi Agung citizen showed siginificant progress, wich was farming community changed to trade and entrepreneur community. This new state, made unbalanced system in society, which they will correct with traditional pattern modification, new pattern or modificate both. This adaptation can be harmonic, adaptive or make friction what makes conflicts (Bee, 1973). Tourism development is vital sectore which government must take obey because it can be supporting variable to achieving development goals. Way Belerang tourist attraction has opened the access of Bumi Agung Village to outside world. This research influenced by processual approach. Man has seen as active, creative and manipulative in the face of his environment. This approach didn’t see the changed linearly, but what has changed and has not and also mechanism and process that takes place what was changed and was not. This research used qualitative method ( Denzin& Lincoln, 2000). Which is tourism industry growth, and developing of Bumi Agung Tourism industry, has made economical and the culture changed to that society, particularly to the livelihoods.